Prototype of Control System for Watering and Spraying Pesticide on Shallot Plants Based on Microcontroller - Istiqomah, Hikmatul; Ariyanti, Dyah; Supraptiningsih, Linda Kurnia (Universitas Panca Marga, 2022)
Shallots are one type of annual plant that belongs to the Liliaceae family. This plant is useful as a seasoning for cooking, as well as a source of much-needed vitamin C, protein, fat, and carbohydrates. On onion plants, there are several things that need to be considered, including watering and spraying pesticides. In watering and spraying pesticides, it is still done manually. Sometimes onion farmers spend too much time and are less efficient in their work, so a water irrigation and pesticide spraying system is made on onion plants on a scheduled basis. This system uses a soil moisture sensor to read data on the amount of water content in the soil, when the sensor detects the soil, the sensor will read moist or dry data. And the Real Time Clock (RTC) functions as a timer, where the specified time has arrived, the RTC will turn on the DC Motor and DC Pump. The DC motor functions as a driving force for the spraying device, and the DC Pump functions as pumping water according to a specified schedule. This system uses an Arduino Uno microcontroller as a controller of the soil moisture sensor and RTC. The result of this research is the formation of watering and spraying pesticides that make it easier for farmers to water and spray pesticides on shallot plants.